Sadd Dzari’ah dalam Perlindungan Investor Pasar Modal Syariah - Djazuli, Saifudien Djazuli; Mujibu Da’wat (Jurnal Iqtisad, 2025)
The Sadd Dzari‘ah principle is understood as an effort to block any means or channel that may lead to what is prohibited (haram). In the context of the Islamic capital market, this principle serves as a preventive pillar that safeguards the purity of Sharia compliance by avoiding riba (usury), gharar (excessive uncertainty), and manipulation. This study aims to analyze how the principle of Sadd Dzari'ah is operationalized as an investor protection mechanism in the Indonesian Islamic capital market through Fatwa DSN-MUI No. 40/DSN-MUI/X/2003, No. 80/DSN-MUI/III/2011, No. 124/DSN-MUI/XI/2018, No. 135/DSN-MUI/V/2020, No. 138/DSN-MUI/V/2020, and No. 157/DSN-MUI/VII/2024. This research employs a normative-comparative approach grounded in uṣūl fiqh and Islamic economic law analysis. The findings reveal that the application of Sadd Dzari‘ah in DSN-MUI fatwas has evolved from a prohibitive principle into an integrative Sharia governance paradigm encompassing investor protection, digital supervision, and the reinforcement of maqāṣid al-sharī‘ah. Each fatwa represents an evolutionary stage of this principle-from the conceptual phase (2003) toward the global-digital regulatory framework (2020–2024). Thus, Sadd Dzari‘ah functions as both a legal and moral instrument for investor protection in Indonesia’s Islamic capital market.